Investigation of Thermal and Spectroscopic Properties of Tellurite-Based Glasses Doped with Rare-Earth Oxides for Infrared Solid-State Lasers - Boussetta, Ahlem; Al-Syadi, Aref M.; Damak, Kamel; Ersundu, Ali Ercin; Ersundu, Miray Celikbilek; Ramadan, Essam; Alshehri, Ali M.; Hussein, Khalid I.; Maalej, Ramzi; Yousef, El Sayed (MDPI, 2024)
The thermal and optical properties of 60TeO2-20K2TeO3-10WO3-10Nb2O5 (in mol%) glasses doped with Ho2O3, Er2O3, and Tm2O3 were explored in the present work. The thermal stability, refractive index n, extinction coefficient k, absorption coefficient alpha, and optical band gap of the glasses were evaluated. The UV-Vis-NIR absorption spectra, the Judd-Ofelt intensity parameter, the spectroscopic quality factor, and the emission and absorption cross-sections were calculated to investigate the effects of Er3+ and Tm3+, respectively, on the band spectroscopic properties of Ho3+ ions. The results showed that the maximum emission cross-section was approximately 8x10-21 cm2, and the values of the full width at half maximum (FWHM), quality factor (sigma exFWHM), and gain coefficient of Ho3+: 5I7 -> 5I8 were also reported. The value of the FWHMx sigma e was 1200x10-28 cm3, which showed greater gain characteristics than earlier study results. For 2 mu m mid-infrared solid-state lasers, the glasses that were examined might be a good host material.
Keywords: co-doped tellurite glasses; rare earth; DSC; thermal properties; refractive index; Judd-Ofelt analysis; gain quality; MU-M EMISSION; NONLINEAR-OPTICAL PROPERTIES; ENERGY-TRANSFER; SELLMEIER COEFFICIENTS; REFRACTIVE-INDEXES; PHOSPHATE-GLASSES; CROSS-SECTION; TM3+; SYSTEM; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics